2008
DOI: 10.3181/0710-mr-287
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Long-Chain Acyl-CoA Synthetases

Abstract: Acyl-CoA synthetase enzymes are essential for de novo lipid synthesis, fatty acid catabolism, and remodeling of membranes. Activation of fatty acids requires a two-step reaction catalyzed by these enzymes. In the first step, an acyl-AMP intermediate is formed from ATP. AMP is then exchanged with CoA to produce the activated acyl-CoA. The release of AMP in this reaction defines the superfamily of AMP-forming enzymes. The length of the carbon chain of the fatty acid species defines the substrate specificity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
324
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(342 citation statements)
references
References 55 publications
8
324
0
Order By: Relevance
“…Therefore, ACSs responsible for S1P metabolism should also be localized in the ER for efficient metabolic flow. It has been reported that each ACS isozyme exhibits characteristic intracellular localization, such as in the ER, plasma membrane, mitochondria, and peroxisome [7,13,14]. However, the precise localization of most ACS isozymes remains unclear since inconsistent localization patterns have been reported among researchers using different approaches.…”
Section: H]dhs Labelingmentioning
confidence: 99%
“…Therefore, ACSs responsible for S1P metabolism should also be localized in the ER for efficient metabolic flow. It has been reported that each ACS isozyme exhibits characteristic intracellular localization, such as in the ER, plasma membrane, mitochondria, and peroxisome [7,13,14]. However, the precise localization of most ACS isozymes remains unclear since inconsistent localization patterns have been reported among researchers using different approaches.…”
Section: H]dhs Labelingmentioning
confidence: 99%
“…VLCFAs are produced from certain LCFAs, provided through diet or generated by FA synthase, or they are elongated from shorter VLCFAs by endoplasmic reticulum (ER) membranebound enzymes, which lengthen each chain with carbon units from FAs that have been converted to substrate-form acyl-CoAs (7). The FA elongase machinery comprises four distinct enzymes.…”
mentioning
confidence: 99%
“…Because trans-2-hexadecenoyl-CoA is classified as a trans-2-enoyl-CoA, the enzyme involved is trans-2-enoyl-CoA reductase. All known enzymes involved in the S1P metabolic pathway are localized in the endoplasmic reticulum (20,(31)(32)(33). Therefore, we expected the candidate trans-2-enoyl-CoA reductase to be localized in the endoplasmic reticulum.…”
Section: Substantial Quantities Of Sph Are Metabolized To Esterlinkedmentioning
confidence: 99%